Determinantes de la participación feminina en las patentes en Brasil: el rol de las corporaciones multinacionales - Marina Filgueiras Jorge (Revista de Economía Mundial)
This study examines female participation in patenting activity across various institutions and the role of multinationals (MN) in this context, exploring the origin of capital and the location of firms, by analyzing patents filed at INPI-Brazil from 2000 to 2019. Despite the increasing number of female inventors, women remain underrepresented in engineering fields, with greater participation in chemistry. MNs contribute to female participation through chemical patents, while national firms and MN subsidiaries focus on engineering, which shows lower female involvement. Public policies promoting women in high-tech sectors and digital entrepreneurship are recommended to address persistent gender disparities in innovation.